DEFORMATION SHRINKAGE AND CREEP OF CONCRETE IN NATURAL CONDITIONS OF DRY HOT CLIMATE - Bakhodir Rizayev, Islombek Akhmedov, Shavkat Yusupov , Isroiljon Umarov, Aleksandir Kazadayev, Farrukh Dadakhanov (Journals Park Publishing, 2022)
This article presents the experimental value of the coefficient of thermal expansion of concrete, shrinkage deformations and creep deformations of concrete in dry and hot climates.
Keywords: shrinkage, creep, stresses, deformation, humidity, temperature, temperature expansion, wet storage, solar radiation, concrete moisture loss, seasonal change, normal conditions